A Man and His Environment, on the Border between Habsburg and Ottoman Empires: Podravina (the River Drava Valley) at Crossroads with MUltiple Borders in Early Modern Period - Petrić, Hrvoje (Array, 2005)
This paper shows an interrelation between man and his environment, on the Habsburg-Ottoman imperial borders in early modern period. As an example, we researched borderline areas alongside Drava River on the Habsburg Monarchy side of the border. This region is primarily the river Drava valley, the term ‘ Podravina’ , ‘ Podravina multiborder area’ (region alongside Drava) was chosen. The center of this region is area surrounding the free royal town of Koprivnica, being the Military Border stronghold and administrative seat at the same time. This &raquo ; ; case stud&laquo ; ; y is an example of a man and his environment in border territory oin early modern period. Chronology data focus on 16th and 17th century, when this area was a frontier to both the Ottoman and Habsburg Empires. The paper focuses on borderline character, which influenced both man and his environment.